Differential Reinforcement of Alternative Behavior Increases Resistance to Extinction: Clinical Demonstration, Animal Modeling, and Clinical Test of One Solution - Mace, F. Charles (Society for the Experimental Analysis of Behavior, Inc, 2010)
Basic research with pigeons on behavioral momentum suggests that differential reinforcement of alternative behavior (DRA) can increase the resistance of target behavior to change. This finding suggests that clinical applications of DRA may inadvertently increase the persistence of target behavior even as it decreases its frequency. We conducted three coordinated experiments to test whether DRA has persistence-strengthening effects on clinically significant target behavior and then tested the effectiveness of a possible solution to this problem in both a nonhuman and clinical study. Experiment 1 compared resistance to extinction following baseline rates of reinforcement versus higher DRA rates of reinforcement in a clinical study. Resistance to extinction was substantially greater following DRA. Experiment 2 tested a rat model of a possible solution to this problem. Training an alternative response in a context without reinforcement of the target response circumvented the persistence-strengthening effects of DRA. Experiment 3 translated the rat model into a novel clinical application of DRA. Training an alternative response with DRA in a separate context resulted in lower resistance to extinction than employing DRA in the context correlated with reinforcement of target behavior. The value of coordinated bidirectional translational research is discussed.